Complementary Metal Oxide Semiconductor-Based Optical Detection System for Fluidic Cellular Medium pH Quantification - André A. Santos; Gabriel M. Ferreira; Paulo J. Sousa; Patrícia C. Sousa; Susana O. Catarino; Graça Minas (Photonics)
Accurate pH sensing is essential for the effective physiological control of the culture media in organ-on-a-chip (OoC) systems. This work proposes a miniaturized optical detection system, based on optical transmittance, for pH level quantification of the EGM™-2 Endothelial Cell Growth Medium-2 BulletKit™ culture medium. Firstly, using a commercial spectrophotometric setup, a set of wavelengths (500, 560, and 600 nm) was selected, as these wavelengths assure distinctive slope variations for the different pH levels. Then, a current-to-frequency converter, based on a low-power Schmitt trigger model with a voltage enhancer, was proposed as the readout electronics and simulated in Cadence Tools using UMC L180 MM/RF technology. A resolution of 0.002 nA was achieved in the linear range of 30 pA to 3800 nA. A miniaturized system composed of a CMOS n-well/p-substrate photodiode and a polydimethilsiloxane (PDMS) microchannel for the culture media substrate was experimentally tested. For a pH range from 6.6 to 6.2, the results clearly demonstrate a magnitude shift of the slope signal, which becomes negative in basic media and positive in acidic media. Additionally, in the 500–560 nm spectral range, the amplitude of the slopes increases for both basic and acidic culture media. In the 560–600 nm range, the slope decreases progressively as the pH of the medium lowers. This miniaturized system was able to quantify the pH of the culture medium, showing potential to be integrated into an organ-on-a-chip device.